Environmental And Health Implications of Waste Disposal Sites In The Lesotho Lowlands - Motaung, Mamello; Roberts, Hester; Makhoahle, Pakiso (Innovation Journal of Social Sciences and Economic Review, 2024)
Many Southern African countries, including Lesotho, face severe health and environmental issues attributed to waste disposal. The purpose of this study is to assessed the environmental and health impacts on residents living in proximity to disposal sites in the lowlands of Lesotho. A descriptive cross-sectional design was employed, using a semi-structured questionnaire and observation method. A mapping device was used, and photographs were taken to validate the findings. Descriptive statistics and the Chi-square test (?²) were employed to analyze the data. Results indicate that in Lesotho, some landfill sites are located as close as 50 meters from residential areas, and most (60%) received hazardous mixed waste streams. Waste burning and backyard dumping were the most frequently used disposal methods by residents. Several perceived health outcomes and environmental issues were noted, with respiratory and gastrointestinal health issues being the most prevalent. There was a statistically significant association between waste burning and respiratory diseases (P < 0.010) and between backyard dumping and gastrointestinal diseases (P < 0.003). The study concludes that regulatory instruments need to be revised and enforced, requiring hazardous waste producers to take responsibility for end-of-life waste and banning the entry of such waste into disposal sites. The application of waste management strategies to initiate other preferable end-of-life waste procedures, such as recycling of WEEE and waste-to-energy technologies for organic waste in Lesotho, could improve the quality of health for residents and their environment.
Keywords: Lesotho urban councils; Waste Disposal; Waste Burning; Dumpsites; Environment Impacts; Health Impacts; Social Impacts